AL- ASY'ARIYAH (STUDI TENTANG PEMIKIRAN AL-BAQILLANI, AL-JUWAINI, AL-GHAZALI) - Muhammad Syarif Hasyim (State Institute of Islamic Studies (IAIN) Palu, 2005)
Theological thought of the Ash’arite founded by Abu Hasan al-Asy'ari develops through its theologians such as al-Baqillani, al-Juwaini, and al-Ghazali. Each of them has his own theological thought that differentiates him from other theologians. However, the three Ash’arite theologians remains to refer to the basic thought of the Asha’rite that make them different from Mu’tazilite theologians, that is, they believe that God has uncreated attributes negated by Mu’tazilte. Kata Kunci: Pemikiran, Teologi, al-Asy’ariyah